THE EFFECTS OF SLEEP DEPRIVATION ON COGNITIVE FUNCTION AND EMOTIONAL REGULATION: AN EXPERIMENTAL APPROACH - Zainol Hasan; Vann Sok; Sokha Dara (World Psychology, 2026)
Sleep is a fundamental biological process that supports cognitive efficiency, emotional stability, and overall psychological well-being. Increasing academic demands, technological engagement, occupational pressures, and lifestyle changes have contributed to a growing prevalence of sleep deprivation across various populations. Insufficient sleep has been associated with impairments in cognitive performance and emotional functioning, yet the interconnected effects of sleep loss on these domains remain insufficiently understood. This study aims to examine the effects of sleep deprivation on cognitive function and emotional regulation through a controlled experimental approach. A randomized controlled pretest-posttest design was employed involving 120 healthy young adults aged 18–25 years. Participants were randomly assigned to either a sleep deprivation group or a control group maintaining a normal sleep schedule. Cognitive performance was assessed using standardized neuropsychological tests measuring attention, working memory, and executive functioning, while emotional regulation was evaluated through validated psychological scales. Statistical analyses included repeated-measures analysis of variance, independent-samples t-tests, and correlation analyses. Findings revealed that sleep deprivation significantly reduced attention, working memory, executive functioning, emotional stability, and positive affect. Significant associations were also identified between declines in executive functioning and impairments in emotional regulation. The study concludes that sleep deprivation exerts a substantial negative influence on both cognitive and emotional processes, highlighting the critical role of adequate sleep in maintaining adaptive psychological functioning and overall well-being.